What is the Management Control System in Timor's Cultural Perspective? - Tuan, Desty Deritha; Wibowo, Eka Adhi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to explore and analyze the cultural values of puah manus and lufut dance among the Timorese in shaping the management control system of companies. The research used ethnographic methods by exploring and interpreting the subjective meanings contained in the culture by conducting interviews with research informants including the director, treasurer, and administration. The study identifies four closely interconnected values influencing the company's management control system. These values include puah manus and lufut dance. The findings underscore the relevance of Timorese cultural values in implementing the company's management control system. This research contributes to advancing a more effective management control system for organizations. The implementation of the puah manus and lufut dance cultures of the Timorese in shaping the management control system is a new area that has not been previously studied. This research is limited to the scope of management control in a company with a Timorese approach and does not compare it with other companies and cultures.